THE RELEVANCE OF LOGIC TO ALTERNATIVE DISPUTE RESOLUTION IN MODERN SOCIETY - Owo, Gideon Idike (EBSU Journal of Social Sciences and Humanities, 2024)
This research examines the relevance of logic on alternative dispute resolution (ADR). The study aims to explore how the use of logical reasoning and critical thinking can contribute to the effectiveness of ADR processes, specifically in mediation and arbitration. The research methodology includes a literature review of existing studies on the subject, as well as a qualitative analysis of interviews with experienced ADR practitioners. The findings suggest that the use of logic in ADR can help to identify and clarify the underlying issues in a dispute, facilitate communication between parties, and support the development of mutually acceptable solutions. The study also highlights the importance of logic in ensuring fairness and impartiality in ADR processes, as well as in the evaluation of evidence and arguments. Based on the results, the research recommends that ADR practitioners receive training in logical reasoning and critical thinking, and that these skills be integrated into ADR processes to enhance their effectiveness. The study concludes that the relevance of logic in ADR is essential for achieving fair, efficient, and satisfactory outcomes in dispute resolution.